Problem uzależnień w Rzeszowie - Pstrąg, Dorota (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The various forms of addiction are considered the most common phenomena of social pathology. The variety of their forms and manifestations as well as the scale of their widespread cause that they become one of the most serious threats affecting contemporary society. They, of course, are present in Rzeszow too, though Podkarpackie is one of the regions characterised by slightly lower rates of these risks than the rest of the country. The text presents the issues relating to the scale of phenomenon of addiction in Rzeszow, and directions and forms of implemented preventive measures. Despite the involvement of a large number of entities within this prevention, it is still too small and its efficiency relatively low. Greater effectiveness of prevention and its adaption to various forms of social needs can ensure the development and application of programs based on more diverse strategies, which are detailed in the text.
Keywords: addiction; prevention strategy